Music library and research skills - Gottlieb, Jane (New Jersey Pearson Prentice Hall, 2009)
Music Library and Research Skills is a complete guide for music majors for researching and completing a paper. It encompasses all the latest technologies and resources, providing not only annotated listings of key items but also informative "how to" side bars and "real life" stories to guide the student. All music majors are required to take a research methods course and this book, by the Vice President and Head Librarian of the Juilliard School, will set a new standard for the course.